Projected Economic Impact of Sediment Removal Programs at Priority Locations - Gultom, Iqbal Suhaemi; Harlis, Triana; Wicaksono, Priagung; Utami, Siti Nuraini Putri; Anggoro, Tri Danny (Faculty of Fisheries and Marine Science, Brawijaya University, 2024)
Removing marine sediment is a Ministry of Marine Affairs and Fisheries program regulated by Government Regulation No. 26 of 2023. Five priority locations have been designated for the removal of marine sediment: Riau Islands Province, West Java Province, East Kalimantan Province, Central Java Province, and East Java Province. This study uses input-output analysis to measure and compare the economic impacts of sediment removal activities on the economies of these five provinces. The input-output table results show that the highest output multiplier for sediment removal activities is in East Kalimantan Province with a value of 1.48, while the lowest is in the Riau Islands Province with a value of 1.22. The highest income multiplier is also found in East Kalimantan Province with a value of 0.3710, followed by Riau Islands Province with a value of 0.3513. In East Kalimantan and Riau Islands, sediment removal is a key sector with strong forward linkages to other sectors but weak backward linkages. One strategy to enhance the economic impact of sediment removal is for the government to spend non-tax state revenue (PNBP) from this activity on key sectors in each province.